Macrophage Kdm6b controls the pro-fibrotic transcriptome signature of foam cells. (April 2017) - Neele, Annette E; Prange, Koen HM; Hoeksema, Marten A; van der Velden, Saskia; Lucas, Tina; Dimmeler, Stefanie; Lutgens, Esther; Van den Bossche, Jan; de Winther, Menno PJ
Aim: In order to identify regulators of foam cells, we studied the H3K27 demethylase Kdm6b (also known as Jmjd3), a known regulator of macrophages, in controlling the transcriptional profile of foam cells.Materials & methods: Foam cells from Kdm6b-deleted or Kdm6b wild-type mice were isolated and used for RNA-sequencing analysis.Results: Pathway analysis revealed that pro-fibrotic pathways were strongly suppressed in Kdm6b-deleted foam cells. Analysis of published datasets showed that foam cell formation induces these pro-fibrotic characteristics. Overlay of both datasets indicated that fibrotic genes which are induced upon foam cell formation, are reduced in the absence of Kdm6b. These data suggest that foam cell formation induces a pro-fibrotic gene signature in a Kdm6b-dependent manner.Conclusion: We identified Kdm6b as a novel regulator of the pro-fibrotic signature of peritoneal foam cells.